Interfering with TGFβ-induced Smad3 nuclear accumulation differentially affects TGFβ-dependent gene expression - Dittmer Jürgen; Nordheim Alfred; Lindemann Ralph K (Molecular Cancer, 2003)
Abstract Background Transforming growth factor-β (TGFβ) plays an important role in late-stage carcinogenesis by stimulating invasive behavior of cancer cells, promoting neo-angiogenesis and by helping cancer cells to escape surveillance by the immune system. It also supports colonization of the bone by metastatic breast cancer cells by increasing expression of osteolytic parathyroid hormone-related protein (PTHrP). Interfering with TGFβ signalling may thus weaken the malignant properties of cancer cells. We investigated to what extent two inhibitors, SB-202190 and SB-203580, interfere with TGFβ-signalling in invasive MDA-MB-231 breast cancer cells. These compounds, formerly used as p38-MAPK-specific inhibitors, were recently also demonstrated to inhibit TGFβ type I receptor kinase. Results Our results show that these inhibitors delay the onset of TGFβ-induced nuclear accumulation of Smad3 and reduces its amplitude. This effect was accompanied by a strong reduction in TGFβ-responsivess of the slow-responder genes pthrp, pai-1 and upa, while the reactivity of the fast-responder gene smad7 to TGFβ remained almost unchanged. Neither was the TGFβ response of the fast-responder ese-1/esx gene, whose expression we found to be strongly downregulated by TGFβ, affected by the inhibitors. Conclusion The data show that SB-202190 and SB-203580 suppress TGFβ-dependent activation of genes that are important for the acquisition of invasive behavior, while having no effect on the expression of the natural TGFβ inhibitor Smad7. This suggests that these compounds are potent inhibitors of malignant behavior of cancer cells.